Evaluations of Case Presentations in Fixed Prosthodontics: Reliability of Examiner Pairings - Amina Elsalhin,; Milad Eshah,; Mohamed Zeglam, (AlQalam Journal of Medical and Applied Sciences, 2022)
Aims. This study evaluates the inter-examiner reliability on student scores when assessing case presentations in Fixed Prosthodontics course. Methods. About 50 CDs were randomly selected from total of 64 CDs and these 50 CD has been distributed to four examiners, 25 CD for each two examiners. Each examiner evaluates the CDs separately. Fourth-year dental students presented their case presentation in CD in group of 4, hence the total of student is 100. Four full time faculty members participated in the evaluation session based on predefined criteria. Grading for rating presentation was scores of 20 marks. The scoring patterns of the evaluators were statistically analyzed using Intra-class coefficient ICC. Results. The results revealed that the obtained ICC value is 0.9493 (indicating excellent reliability) and its 95% confidence interval ranges between 0.9246 and 0.9659, meaning that there is 95% chance that the true ICC value lands on any point between 0.9246 and 0.9659. The results also revealed that the consistency between examiner 3 and 4 was more strong than examiner 1 and 2. Conclusion. The study concluded that excellent consistency among examiners (inter reliability) were persist. The results also revealed that the consistency between examiner 3 and 4 was higher than examiner 1 and 2. Cite this article: Elsalhin A, Eshah M, Zeglam M. Microfacies Evaluations of Case Presentations in Fixed Prosthodontics: Reliability of Examiner Pairings. Alq J Med App Sci. 2022;5(2):580-584. https://doi.org/10.5281/zenodo.7443381